2014
DOI: 10.1177/0883073814535496
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges of Fetal Cisterna Magna Length and Area Measurements by 3-Dimensional Ultrasonography Using the Multiplanar Mode

Abstract: This study aimed to establish reference values for the length and area of the fetal cisterna magna using the multiplanar mode of 3-dimensional ultrasonography. A cross-sectional study including 224 normal pregnant women between 17 weeks 0 days and 29 weeks 6 days of gestation was carried out. The area and length of the fetal cisterna magna were measured in the axial plane at the level of the cerebellar transverse diameter. Reliability was determined by intraclass correlation coefficient. The mean length and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
“…Excluded studies and reasons for exclusion are reported in Table S3 . Finally, 42 studies, reported between January 1970 and 2021, met the inclusion criteria, and these provided data for 45,626 fetuses, included in the final analysis ( Table 1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The median sample size of participating fetuses was 372.5 (range: 50 to 8313; 25th percentile: 175.8; 75th percentile: 709.3).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Passos et al (2014) established reference ranges for fetal cisterna magna length and area by 3-DUS in the multiplanar mode in 224 normal pregnancies between 17 and 30 wk of gestation. The authors found that the mean length and area of the fetal cisterna magna ranged from 0.50 6 0.10 to 0.79 6 0.18 cm and from 0.95 6 0.18 to 3.09 6 0.62 cm 2 , respectively.…”
Section: -D Ultrasound and The Study Of Fetal Brain Anatomy: ''The Nmentioning
confidence: 99%
“…This means that the cutoff value of 10 mm provides a good measure between 18 and 23 weeks of gestation but is probably somewhat too high early in gestation, and too low later. There are reference values for the area and length [34], as well as the volume of the cisterna magna [35].…”
Section: Cisterna Magnamentioning
confidence: 99%